REPRESENTASI HEGEMONI KEKUASAAN DAN NILAI HUMANISME PADA ZAMAN KOLONIALISME DALAM NOVEL GERHANA MERAH KARYA MUHAMMAD SHOLIHIN - Inaayatul Chusna; Muhammad Noor Ahsin; Agus Darmuki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social reality serves as an inspiration for the creation of literary works while also revealing the meaning of every event that occurs. Novel is a form of literary work that reveals the social reality of society as constructed by the author, one aspect of which is the imbalance of power. Novel Gerhana Merah by Muhammad Sholihin depicts the ethnic tensions of the Minangkabau people resulting from foreign colonization during the colonial era. This study aims to explain the representation of hegemonic power in the novel Gerhana Merah by Muhammad Sholihin. It also aims to explain the representation of humanist values in the novel. The representation of hegemonic power was analyzed using Gramsci's theory of hegemony, while data on humanist values were obtained using Freire's theory. This study employs a descriptive qualitative method, with data collected through reading and note-taking techniques applied to dialogues and narratives containing elements of hegemonic power and humanist values. Furthermore, the data analysis technique involved three stages: data reduction, data presentation, and conclusion drawing. The results of the analysis show that, based on Gramsci's theory, there are nine forms of hegemonic power instruments manifested through language, common sense, and folklore that influence the characters in the novel. The application of Freire's theory reveals nine forms of humanist values, manifested as acts of struggle to uphold humanity in response to oppression, reflecting the characters' consciousness in the novel such as justice, solidarity, and moral resistance.